Incorporating industrial design pedagogy into a mechanical engineering graphics course: a discipline-based education research (DBER) approach - Sunni Newton; Meltem Alemdar; Ethan Hilton; Julie Linsey; Katherine Fu (SpringerOpen, 2018)
Abstract Background A redesigned curriculum for teaching engineering graphics was adopted in an introductory mechanical engineering course. The rollout of this curriculum was staggered, allowing for comparisons of student perceptions across the newly revised and previous instructional approaches. The new curriculum borrows from content and pedagogy traditionally employed in industrial design courses. The discipline-based education research (DBER) framework was used to investigate the manner in which the new curriculum was implemented and student reactions to this change. By using this approach, the researchers were able to incorporate and emphasize the unique aspects of the subject matter itself, as well as the attributes of the engineering discipline in which the course was embedded. Results Results indicated that students exhibited positive reactions to the sketching instruction, as well as various other aspects of the course, and that reactions were generally more positive among students in the redesigned course. Conclusions The contributions of this paper are twofold: illustrating the application of a specific research framework and providing results of an investigation of a redesigned curriculum. The redesigned curriculum was generally received well by students, and the partnership between the education researchers and faculty proved fruitful in allowing for nuanced investigation of the course redesign. Practical considerations for undertaking this type of research are also outlined.